Human resources selection in business processes supported by BPMS: optimizing work performance - Uahi, Robbie (2017)
Business Process Management (BPM) has become a major topic in the modern management literature and research. Underlying BPM is the concept of business process. Due to the high acceptance of the BPM principles and its worldwide adoption by organizations, a specific class of software platforms has emerged - the so-called Business Processes Management Systems (BPMS). These systems aim to support BPM by managing the execution of business processes. In doing so, BPMS deliver the work activities to the human resources or Information Technology (IT) automatisms used to perform them. Regarding the delivering of work to human resources, nowadays BPMS use a very simplistic approach: any person registered in the system as allowed to perform a certain activity (process modelling phase) is automatically a candidate to perform that activity in the process execution phase. Obviously, this resource selection mechanism assures that work is executed only by who may execute it, but doesn’t guarantee that work is executed by who is “best” prepared to execute it. We claim that, to achieve maximum organizational performance, it is necessary to compare the characteristics of each work activity that has to be executed and the characteristics of the human resources that are allowed to perform it, always selecting the most suitable candidate. In this context, the so-called Personality Assessment Frameworks have an important role in helping to “profile” human resources, thus providing the tools to characterize each person. In this paper we discuss the relevant aspects to be taken into account in the allocation of work activities to human resources, in order to optimize the performance of business processes supported by BPMS. The aim is to prepare BPMS with the means to, automatically, select the most qualified person to perform each work activity.